1989
DOI: 10.1007/bf01671163
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of distal splenorenal shunt in the treatment of esophageal varices: An analysis of prophylactic, emergency, and elective shunts

Abstract: From June, 1969 to February, 1987, distal splenorenal shunt was carried out on 78 patients with esophagogastric varices. The operations were urgent in 9, elective in 40, and prophylactic in 29 patients. There were 52 males and 26 females. Age ranged from 16 to 76 years with an average of 53 years. Thirty-seven patients were alcoholics. Hepatitis B surface antigen was positive in only 15.5%. The causes of portal hypertension were cirrhosis of the liver in 67, chronic hepatitis in 5, idiopathic portal hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
(25 reference statements)
0
17
0
1
Order By: Relevance
“…Treatment strategies for esophagogastric varices have undergone significant changes in the past decades. Nonselective shunting procedures had been progressively abandoned owing to serious deterioration in quality of life due to devastating encephalopathy and hepatic failure 46–48 . As a result, selective distal splenorenal shunt, which preserves portal blood flow, has been more widely accepted as the definite surgical management in western countries, based on its lower incidence of post‐shunting encephalopathy and accelerated liver failure from reduced hepatic perfusion 46,47 .…”
Section: Indication Of Splenectomy In Hepatic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment strategies for esophagogastric varices have undergone significant changes in the past decades. Nonselective shunting procedures had been progressively abandoned owing to serious deterioration in quality of life due to devastating encephalopathy and hepatic failure 46–48 . As a result, selective distal splenorenal shunt, which preserves portal blood flow, has been more widely accepted as the definite surgical management in western countries, based on its lower incidence of post‐shunting encephalopathy and accelerated liver failure from reduced hepatic perfusion 46,47 .…”
Section: Indication Of Splenectomy In Hepatic Disordersmentioning
confidence: 99%
“…As a result, selective distal splenorenal shunt, which preserves portal blood flow, has been more widely accepted as the definite surgical management in western countries, based on its lower incidence of post‐shunting encephalopathy and accelerated liver failure from reduced hepatic perfusion 46,47 . However it has subsequently been reported that the selectivity of distal sprenorenal shunting is lost with time because of new venous collaterals around the peripancreatic or gastrosplenic parts 48–51 . Surgical difficulties in freeing the huge splenic vein from the inflamed surrounding tissues have made surgeons reluctant to perform this surgery, especially in Japan 52 …”
Section: Indication Of Splenectomy In Hepatic Disordersmentioning
confidence: 99%
“…Nesse mesmo estudo (9) , em que se revisou retrospectivamente a recidiva hemorrágica nos pacientes Child A e B operados pela técnica de Teixeira-Warren, observou-se que a percentagem de ressangramento (56%) foi mais acentuada do que na literatura (3,8% -14%) (13,15,16,17,21,28) . Atribui-se esse índice ao elevado número de doentes Child B e de cirrose por álcool.…”
Section: Resultsunclassified
“…The pooled mortality for patients with Child' s class A cirrhosis undergoing DSRS was 2.9% in the first year and 12.0% in the second year of the model. 12,13 The pooled mortality for patients with Child' s class A cirrhosis undergoing TIPS was 5.7% in the first year and 10.9% in the second year of the model. 10,14,15,16 A sensitivity analysis was used to address the issue of the wide range of survival statistics.…”
Section: Methodsmentioning
confidence: 99%